A retrospective multi‐center experience of renal transplants from India during COVID‐19 pandemic. Issue 10 (19th July 2021) - Jha, Pranaw Kumar; Yadav, Dinesh Kumar; Siddini, Vishwanath; Bansal, Shyam Bihari; Sharma, Reetesh; Anandh, Urmila; Jeloka, Tarun; Reddy, Sreedhar; Pokhariyal, Saurabh; Nandwani, Ashish; Jain, Salil; Saxena, Vishal; et al.
Abstract: Introduction: Coronavirus disease 2019 (COVID‐19) pandemic led to a sudden drop in renal transplant numbers across India in the initial months of 2020. Although the transplant numbers increased with easing of lockdown, the outcome of these transplants remains unknown. Methods: This was a retrospective, observational, multi‐center study done across eight different transplant centers in India. All the transplants done from January 30, 2020 to December 31, 2020 were included. The primary outcomes studied were patient and death censored graft survival as well as incidence of COVID‐19 infection and its outcomes. Results: During the study period a total of 297 kidney transplants were done. After a median follow up of 265 days the patient and death censored graft survival was 95.3% and 97.6%, respectively. Forty‐one patients (13.8%) developed COVID‐19 post‐transplant. Majority (58.5%) were asymptomatic to mildly symptomatic and the case fatality ratio was 14.6%. On multivariable logistic regression analysis older age was associated with higher likelihood of COVID‐19 infection (odds ratio 1.038; CI 1.002–1.077). Conclusions: Patient and graft outcome of kidney transplants done during the COVID‐19 pandemic in India was acceptable. The incidence of COVID‐19 was 13.8% with a high case fatality ratio.